Pengaruh Pengalaman Kerja, Independensi, Kompetensi Dan Integritas Terhadap Kualitas Audit: ( Studi Empiris Pada Inspektorat Provinsi Lampung ) - Daniel Daniel; Haninun Haninun (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
This study has the objective of showing empirically the effect of work experience, independence, competence and integrity on audit quality. In this study, there are 1 independent variable, namely audit quality and 4 dependent variables, namely work experience, independence, competence and integrity. The population of this study is the Inspectorate of Lampung Province in 2022. The data was obtained using a proposive sampling technique. The samples obtained by using a proposive sampling technique were 60 auditors. The data collection method is a questionnaire. This study shows the results that work experience, independence, competence and integrity have a positive influence on audit quality.